Ocena przydatności maszyn podczas zrywki drewna w drzewostanach sosnowych na podstawie podstawowych wskaźników pracy - Szewczyk, Katarzyna; Iwanicki, Piotr (Leśne Prace Badawcze, 2019)
Skidding of large-sized logs requires special machinery such as skidders, clambunks, forwarders or farm tractors with a winch or hydraulic tongs. The precise choice of which skidding machine to use depends largely on the desired efficiency and economic factors. The aim of this research was to evaluate the suitability of three different machines (LKT 81 skidder, John Deere 1110D forwarder and Pronar 1221A agricultural tractor with hydraulic tongs) for wood skidding based on technical and economic indicators. The practical work for this research was carried out in the Mirosławiec Forest Division in areas with fresh mixed coniferous forest habitats where the dominant species in the stands was pine and strip-like clear cutting the preferred management practice. The best machinery performance values were obtained for skidding using the John Deere forwarder.